MANAJEMEN PENGETAHUAN SISTEM INFORMASI PEGAWAI PT GUNA KARYA INDONESIA (GKI) BEKASI - Sugiyono Sugiyono (CKI ON SPOT, 2017)
Knowledge  management  system  at  PT  Guna  Karya  Indonesia  has  tacit  knowledge  and  explicit knowledge by transferring directly to the employees without any storage media, so that such a system is felt to have constraints because not all employees obtain or know the knowledge, although there is no storage of knowledge  then  it  is  feared  that  the  transferred  knowledge  will  just  disappear.  In  addition  there  is  no knowledge  sharing  application  that  can  allow  a  person  to  interact  or  share  knowledge  wherever  and whenever, for example a discussion forum currently running at PT Guna Karya Indonesia is by way of meeting or meeting directly (face to face) also criticisms and advice  employees in issuing criticisms or suggestions are done manually  like is by talking directly to other employees. Surely this will take more time and effort and another with training or workshop system does not have storage media and the lack of knowledge transfer training to employees who do not attend the training does not know the results of the training.